MEMOTIVASI PERILAKU HEMAT ENERGI DAN RAMAH LINGKUNGAN DI SEBUAH HOTEL - Wayan G. Santika (Bumi Lestari Journal of Environment, 2013)
AbstrakThe present study aimed to find out whether persuasive messages with descriptive normsand norms of reciprocation were better than the standard message in increasingparticipation in hotel’s reuse linens and towels program and to know whether similarstudies conducted in the individualistic culture of the United States could be replicated forthe Indonesian collectivistic culture. The study started by printing four different cards withstandard, standard with bigger fonts, descriptive norms, and norms of reciprocationmessages. Cards were placed in rooms of a hotel located in Bali. Results show that cardsprinted with descriptive norms and norms of reciprocation messages were indeed moredominant than the standard one in increasing participation in linens and towels reuseprogram. The results were similar to those conducted in the United States.